PROFIL POLA USAHA TAMBAK RAKYAT POLIKULTUR KEPITING BAKAU DAN IKAN BANDENG DI KELURAHAN PADANG SERAI PULAU BAAI KOTA BENGKULU - Citra Susantri Putri Sirait; Eko Sumartono (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2017)
This research conducted at padang serai sub-district RT 04 RW 04 in bengkulu city on february 2017. The objectives of this research were the farmer of mangrove crab and milkfish fish in Padang Serai Sub-District Bengkulu City. The location of the research was chosen by using purposive method and the respondents were chosen by using census method. The number of respondents were 5 people. Analytical methods used in this research were Descriptive analysis is case study. The results of the research Polyfish farming business of polyculture of mangrove crabs and bendeng fish in Padang Serai urban village when Prapasca business pattern starts from site selection, preparation of equipment, pond preparation by draining ponds, TSP and urea fertilizer, water filling then cage fertilization. Then the preparation of seeds, seeds used are seeds of mangrove crab and milkfish. Then carried out the maintenance by way of feeding and penaganan of pests in the form of the theft of business products. Harvesting products of mangrove crab and milkfish for milkfish only do total harvest while the mangrove crab is done by partial harvesting and total harvesting. Post-harvest handling is to do marketing of mangrove crabs to eat houses and for milkfish sold to pack rusan as pengumpul and to traders, the surrounding community who came to buy to the location.